Information Hiding in Color Image Using Steganographic technique (Journal of the College of Basic Education, 2022)
Steganography is one of the important research subjects in the field of information security. It enables secret communication by embedding messages in the texts, images, audio, video files or other digital carriers. Among all the image information hiding methods, LSB embedding is widely used for its high hiding capacity and it is with great significance to detect the images with hidden messages produced by LSB embedding effectively, accurately and reliably. Therefore, many experts made efforts on the LSB steganography and steganalysis research over the years. This research presents a steganographic technique based on using LSB of one of the pixel color components in the image and changes them according to the message’s bits to hide. The rest of bits in the pixel color component selected are also changed in order get the nearest color to the original one in the scale of colors. This new method has been tested with others that work in the spatial domain through applying some common metrics which give us good result as a compared with the other steganographic tools.